2010
DOI: 10.1074/jbc.m109.088153
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-based Transcriptional and Epigenetic Profiling of Matrix Metalloproteinases, Collagens, and Related Genes in Cancer

Abstract: Epigenetic parameters (DNA methylation, histone modifications, and miRNAs) play a significant role in cancer. To identify the common epigenetic signatures of both the individual matrix metalloproteinases (MMPs) and the additional genes, the function of which is also linked to proteolysis, migration, and tumorigenesis, we performed epigenetic profiling of 486 selected genes in unrelated non-migratory MCF-7 breast carcinoma and highly migratory U251 glioma cells. Genome-wide transcriptional profiling, quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 58 publications
1
45
0
Order By: Relevance
“…Functional clustering was conducted using Ingenuity Pathway Analyses (Qiagen). The association of genes with biological functions and canonical pathways was based on the respective p-values, calculated using the right-tailed Fisher exact test [40]. …”
Section: Methodsmentioning
confidence: 99%
“…Functional clustering was conducted using Ingenuity Pathway Analyses (Qiagen). The association of genes with biological functions and canonical pathways was based on the respective p-values, calculated using the right-tailed Fisher exact test [40]. …”
Section: Methodsmentioning
confidence: 99%
“…These deficiencies become especially important as several MMPs, including MMP-8 and, potentially, MMP-19 and MMP-25, demonstrate anti-tumor properties and thus should not be pharmacologically targeted in certain malignancies while the function of multiple additional MMPs remains unknown in disease context (Chernov, et al, 2010; Chernov and Strongin, 2011; Coussens, et al, 2002; Gutierrez-Fernandez, et al, 2008; Overall and Kleifeld, 2006; Shay, et al, 2015). Precise knowledge of the MMP cleavage preferences is needed to rationally relate MMPs to the cleaved substrates.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that the proMMP-1 gene expression requires chromatin remodeling in part via histone posttranslational modifications (18)(19)(20)(21)(22). A previous study showed that proMMP-1 gene expression induced by TPA in T98G cells involved a dynamic and ordered recruitment of enzymes allowing H3/H4 acetylation, H3K4 di-and trimethylation, H3S10 phosphorylation and chromatin opening (22).…”
Section: Introductionmentioning
confidence: 99%